2022
DOI: 10.1186/s13018-022-03414-9
|View full text |Cite
|
Sign up to set email alerts
|

Anterosuperior approach versus deltopectoral approach for reverse total shoulder arthroplasty: a systematic review and meta-analysis

Abstract: Background Surgical approach is an important factor that may affect the outcomes of reverse total shoulder arthroplasty (RTSA). The most common approaches for RTSA are anterosuperior (AS) and deltopectoral (DP). However, controversy exists on which surgical approach is better. This meta-analysis aimed to compare both approaches in terms of radiological and clinical outcomes and complications. Methods We searched PubMed, Embase, and Cochrane Library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
4
1
Order By: Relevance
“…Humeral stem 25 (13) of 136 cases from two studies, Seok et al 16 found a lower rate of glenoid loosening with the anterosuperior approach (odds ratio 0.10 (95% CI 0.01 to 0.93)), which is similar to our initial bivariable model. However, the CI approaches 0, suggesting a poor correlation.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Humeral stem 25 (13) of 136 cases from two studies, Seok et al 16 found a lower rate of glenoid loosening with the anterosuperior approach (odds ratio 0.10 (95% CI 0.01 to 0.93)), which is similar to our initial bivariable model. However, the CI approaches 0, suggesting a poor correlation.…”
Section: Discussionsupporting
confidence: 85%
“…8 Several studies have compared the complications between the two approaches (Table I). 6,[9][10][11][12][13][14][15][16] Some studies have linked the anterosuperior with a lower postoperative instability rate compared to the deltopectoral approach, which is attributed to preserving the subscapularis and anterior ligament complex. 5,6 Previous studies have also associated the anterosuperior approach with a more superior placement and superior tilt of the metaglene compared to the deltopectoral approach.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference in follow-up time may be a source of bias, however, a previous study found no significant changes in results after 1 year, which was the minimum follow-up in this study [8]. Furthermore, the approach differed between the groups (the anterosuperior approach was used for regular RSA and the deltopectoral approach for BIO-RSA); however, the approach did not influence outcomes in previous studies [40,41]. Second, bone graft healing and viability, and implant positioning is best assessed on computed tomography (CT) scans instead of radiographs.…”
Section: Limitationscontrasting
confidence: 52%